2012
DOI: 10.1086/666593
|View full text |Cite
|
Sign up to set email alerts
|

RR Lyrae Variables in the Ultraviolet: The View from GALEX

Abstract: serendipitously obtained with the NASA GALEX satellite that show changes of up to AB ¼ 6:5 mag in the far-ultraviolet (FUV; 1350-1800 Å) wavelength band. For the test case SW Aqr, we combine the GALEX FUV and NUV (1800-2800 Å) observations with visible U, B, and V photometry to determine the variation of physical parameters such as temperature, surface gravity, and radius during the RR Lyrae pulsation cycle of 0.459299 days. Assuming that SWAqr changes temperature from 6100 K to 8400 K over this cycle, we find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 17 publications
(19 reference statements)
3
17
0
Order By: Relevance
“…The NUV pulsation amplitude of RR Lyrae stars is roughly twice that of their V amplitude (as found earlier by Wheatley et al 2012). This allows us to detect low-amplitude variables such as J013642.0−062743.1 and J171251.8+185452.4 which have V amplitudes of 0.25 and 0.38 mag, respectively.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The NUV pulsation amplitude of RR Lyrae stars is roughly twice that of their V amplitude (as found earlier by Wheatley et al 2012). This allows us to detect low-amplitude variables such as J013642.0−062743.1 and J171251.8+185452.4 which have V amplitudes of 0.25 and 0.38 mag, respectively.…”
Section: Discussionsupporting
confidence: 78%
“…Wheatley et al (2012) fit model light curves to the FUV and NUV photometry of six well-observed bright RR Lyrae stars. They find that the FUV and NUV light curves, which primarily reflect temperature changes during the pulsation cycle, also depend on metallicity.…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic variability declines with the increase of T eff , implying that late-type stars tend to have strong variabilities. The σ int values in the FUV are generally larger than those in the NUV, probably due to the higher amplitudes of light curves in the shorter wavelength (Wheatley et al 2012). Another parameter to characterize the variability is the structure function (see di Clemente et al 1996 for details),…”
Section: Variability Statisticsmentioning
confidence: 99%
“…However, the color of the (NUV − J) can separate M giants from M dwarfs in Figure 15. Here we use a robust linear separation, the lowest density of the stars in the diagram of molecular-band indices in Figure 16 of 2−5 mag (Wheatley et al 2012), making them more likely to be detected in the UV. They are thus popular tracers of Galactic structures, the halo and streams (Drake et al 2013).…”
Section: Colors Of Giant and Dwarf Starsmentioning
confidence: 99%
“…M dwarf flare stars have strong magnetic activity that manifests itself in flares of thermal UV emission on the timescale of minutes (Kowalski et al 2009). RR Lyrae stars have periodic pulsations which drive temperature fluctuations from ∼ 6000 to 8000 K that cause periodic variability in the UV on a timescale of ∼ 0.5 d (Wheatley et al 2012). Core-collapse supernovae (SNe) remain bright in the UV for hours up to several days following shock breakout, depending on the radius of the progenitor star (Nakar & Sari 2010;Rabinak & Waxman 2011), and the presence of a dense wind (Ofek et al 2010;Chevalier & Irwin 2011;Svirski et al 2012).…”
Section: Introductionmentioning
confidence: 99%